Species pool and local assembly processes drive microbial β diversity in primary forest soils - Debao Li; Jianping Wu (Global Ecology and Conservation)
Primary forests occupy high biodiversity, where the α diversity of both above- and below-ground has been well studied. Nevertheless, our current knowledge of the β diversity in below-ground is limited. To examine the mechanisms driving patterns of β diversity in soil microbes, we collected soil samples from three typical tropical, subtropical, and temperate primary forests in southwest China. Results indicated the highest soil bacterial and fungal β diversity in the tropical forest, lowest bacterial β diversity in the subtropical forest, and lowest fungal β diversity in the temperate forest. Community assembly, regional species pools, and microbial interactions jointly shaped soil bacterial β diversity patterns. Soil fungal β diversity patterns were influenced by regional species pools and community assembly. Furthermore, microbial β diversity was closely correlated to soil microbial metabolism, carbon cycling, and nitrogen cycling functional potentials. Our study emphasizes that not only soil microbial α diversity, but also β diversity attribute to carbon and nitrogen biochemical cycling, which provides new insight for the connections between microbial diversity maintenance and ecosystem functions in old-growth forests.